2005
DOI: 10.1111/j.1399-3054.2005.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time RT‐PCR analysis of loblolly pine (Pinus taeda) arabinogalactan‐protein and arabinogalactan‐protein‐like genes

Abstract: Arabinogalactan-proteins (AGPs) are a class of large hydroxyproline-rich glycoproteins (HGRPs) found in almost all plant species, and have been implicated in various plant growth and developmental processes including xylogenesis. A total of six AGP-like genes or gene families have been cloned from differentiating pine xylem. In this study, seven different members of the ptaAGP5 gene family with between 54% and 73% similarity at the amino acid level were newly identified. Gene-specific primers were designed and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 71 publications
1
19
0
2
Order By: Relevance
“…, 2004). By contrast, AGP5 transcript is preferentially accumulated in LW of radiata (this study) and loblolly pine (Yang & Loopstra, 2005; Yang et al. , 2005).…”
Section: Discussionmentioning
confidence: 46%
“…, 2004). By contrast, AGP5 transcript is preferentially accumulated in LW of radiata (this study) and loblolly pine (Yang & Loopstra, 2005; Yang et al. , 2005).…”
Section: Discussionmentioning
confidence: 46%
“…In loblolly pine six PtaAGPs were predominantly transcribed in secondary xylem development [46]. Our study revealed that FLAs were differentially transcribed in either CW ( FLA1 and 8 ) or OW ( FLA10 , 17 and 26 ) of radiata pine branches.…”
Section: Discussionmentioning
confidence: 74%
“…Consistent with our localization results, Zhang et al (2003) have previously shown that PtaAGP6 epitopes preceded secondary wall deposition in loblolly pine. Several AGP genes have also been shown to be highly expressed in diVerentiating xylem from loblolly pine (Loopstra and SederoV 1995;Loopstra et al 2000;Zhang et al 2003;Yang et al 2005). Moreover, the addition of AGPs to Zinnia cultures has been shown to stimulate xylogenesis (Motose et al 2004).…”
Section: Agps and Tracheid Diverentiationmentioning
confidence: 95%